ADSORPTION BEHAVIOR OF Pb (II) ON GAMALAMA VOLCANIC SOIL: KINETIC AND ISOTHERM STUDIES - Indra Cipta; Nur Jannah Baturante; Hernawan Hernawan; M. Hidayat Jaya Miharja; Nur Fadillah Putri Saiful (Walisongo Journal of Chemistry, 2026)
Lead (Pb) contamination in aquatic environments poses serious risks to ecosystems and human health due to its toxicity and persistence. This study evaluates the potential of Gamalama volcanic soil (GVS), a locally abundant aluminosilicate material, as a low-cost adsorbent for Pb(II) removal. Batch adsorption experiments were conducted at initial Pb(II) concentrations of 50–500 mg/L and contact times of 20–120 min. Adsorption behavior was analyzed using kinetic models, namely the pseudo-first-order and pseudo-second-order models, and isotherm models, namely the Langmuir and Freundlich models. The structural and surface properties of GVS before and after adsorption were characterized by FTIR, XRD, and N₂ adsorption (BET). The adsorption efficiency decreased from 45.8% to 33.6% with increasing initial Pb(II) concentration, indicating progressive saturation of active sites. In contrast, adsorption increased with contact time and reached a maximum of 94.87% at 60 min. Kinetic analysis showed an excellent fit to the pseudo-second-order model (R² = 0.9997), suggesting a chemisorption-controlled process. The Freundlich isotherm provided a better fit (R² = 0.9902), indicating multilayer adsorption on heterogeneous surfaces. XRD patterns showed no significant changes after adsorption, while the BET surface area decreased from 490.128 to 464.707 m²/g, suggesting partial pore blockage. These results demonstrate that GVS is a promising natural adsorbent for Pb(II) removal, although further studies on selectivity and regeneration are required for practical applications.